(untitled) ("Temas Sociais" Journal, 2023)
The debate on the stereotyping of Brazilian women in Portugal is of great importance, given the social damage it can cause to their lives. Brazilian women account for the highest proportion of all immigrant groups in Portugal. Unfortunately, it is not new that they are stigmatised due to their personality and physical characteristics, which in many situations influence the emergence of discrimination. With this in mind, the main aim of this research was to understand the social representation of Brazilian women in Portugal and whether there are any stereotypes linked to them. To this end, an exploratory study with descriptive characteristics was conducted, using surveys to interview the Portuguese population in Coimbra. The study found that the majority of participants believe that Brazilian women have specific personality and physical characteristics, the latter being linked to sensuality and sexuality. The majority believe that Brazilian women are linked to particular professional areas, namely prostitution and beauty. Finally, they believe there is a stereotype linked to Brazilian women that associates them with easy sex. Thus, being a Brazilian immigrant woman in Portugal means being at a complicated crossroads between different social demarcations, where prejudice, discrimination and sexism end up marking their lives.